2020
DOI: 10.7759/cureus.11771
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis Is Associated With an Increased Risk of Hospitalization for Systemic Lupus Erythematosus: Analysis of the National Inpatient Sample Database

Abstract: Background: There is a scarcity of literature on co-existing psoriasis (Ps) and systemic lupus erythematosus (SLE). We used a large national population database to determine if there is any association between Ps and SLE. The primary objective was to compare the odds of being admitted for SLE in patients with Ps compared to those without Ps. The secondary objective was to compare hospital outcomes of patients admitted for SLE with co-existing Ps to those without Ps. Methods: Data were abstracted from the Natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Also, ICD‐9‐PCS codes 990* and ICD‐10‐PCS codes 320* were used to identify patients who received blood transfusion (Red blood cell, Plasma, and Platelet). All the codes have been verified in previous studies 15–20 …”
Section: Methodsmentioning
confidence: 68%
“…Also, ICD‐9‐PCS codes 990* and ICD‐10‐PCS codes 320* were used to identify patients who received blood transfusion (Red blood cell, Plasma, and Platelet). All the codes have been verified in previous studies 15–20 …”
Section: Methodsmentioning
confidence: 68%
“…A previous study, investigating the prevalence of PS in patients with principally diagnosed SLE, analyzed a large national population database for admission probabilities of patients with SLE, and demonstrated that 150 of a total of 20,630 hospitalized patients with SLE (0.7%) had a co-existing PS condition (40). In another study, it was reported that 0.6% of 520 patients with SLE had PS (41).…”
Section: Prevalence Of Ps In Patients With Preexisting Slementioning
confidence: 99%